Structural and optical properties of brominated plasma polymers - Appolinario, Marcelo Borgatto [UNESP]; Oliveira Neto, Antonio Mendes de [UNESP]; Schreiner, Wido H.; Cruz, Nilson C. da [UNESP]; Rangel, Elidiane C. [UNESP]; Durrant, Steven F. [UNESP] (Elsevier B.V., 2013)
Novel brominated amorphous hydrogenated carbon (a-C:H:Br) films were produced by the plasma polymerization of acetylene-bromoform mixtures. The main parameter of interest was the degree of bromination, which depends on the partial pressure of bromoform in the plasma feed, expressed as a percentage of the total pressure, R-B. When bromoform is present in the feed, deposition rates of up to about 110 nm min(-1) may be obtained. The structure and composition of the films were characterized by Transmission Infrared Reflection Absorption Spectroscopy (IRRAS) and X-ray Photo-electron Spectroscopy (XPS). The latter revealed that films with atomic ratios Br:C of up to 0.58 may be produced. Surface contact angles, measured using goniometry, could be increased from similar to 63 degrees (for an unbrominated film) to similar to 90 degrees for R-B of 60 to 80%. Film surface roughness, measured using a profilometer, does not depend strongly on R-B. Optical properties the refractive index, n, absorption coefficient, alpha(E), where E is the photon energy, and the optical gap, E-g, were determined from film thicknesses and data obtained by Transmission Ultraviolet-Visible Near Infrared Spectroscopy (UVS). Control of n was possible via selection of R-B. The measured optical gap increases with increasing F-BC, the atomic ratio of Br to C in the film, and semi-empirical modeling accounts for this tendency. A typical hardness of the brominated films, determined via nano-indentation, was similar to 0.5 GPa. (C), 2013 Elsevier B.V. All rights reserved.
Keywords: PECVD; a-C:H:Br; Plasma polymer; Optical properties; Tauc gap